Medium-, long- and medium-chain-type structured lipids ameliorate high-fat diet-induced atherosclerosis by regulating inflammation, adipogenesis, and gut microbiota in ApoE−/− mice. Issue 6 (20th May 2020) - Yue, Chonghui; Li, Ming; Li, Jing; Han, Xu; Zhu, Hongwei; Yu, Guoping; Cheng, Jianjun
Abstract : MLM structured lipids synthesized from corn oil and caprylic slow down atherosclerosis induced by high fat diet via regulating inflammation, adipogenesis and gut microbiota. Abstract : Accumulating evidence has suggested that medium-, long-, and medium-chain (MLM) structured lipids have anti-obesity effects, but whether they can alleviate the development of atherosclerosis (AS) and affect the composition of the gut microbiota in high-fat diet-fed ApoE −/− mice has not been elucidated. The present study found that MLM structured lipid supplementation could significantly decrease obesity-related parameters compared with high-fat diet alone in ApoE −/− mice. Additionally, MLM structured lipids could significantly decrease the blood glucose and increase the serum total antioxidant capacity (T-AOC) and superoxide dismutase (SOD) levels. Additionally, high-dose MLM structured lipids supplementation could reduce the area of atherosclerotic lesions and decrease the expression of VCAM-1, MCP-1 and CD68, which are related to inflammation in aortic tissue. Further analysis showed that MLM structured lipids could significantly reduce lipid accumulation in the adipose tissue of high-fat diet-fed ApoE −/− mice. The relative protein expression of SREBP-1, ACC, FAS, C/EBPα and PPARγ was decreased and the ratio of p-AMPK/AMPK was increased in epididymis white adipose tissue (eWAT) after MLM structured lipids treatment. Additionally, MLM structured lipids supplementation regulated the bacterial composition, including reducing the Firmicutes / Bacteroidetes ratio, increasing the relative abundance of short-chain fatty acid-producing bacteria ( Blautia and Anaerotruncus ), decreasing the relative abundance of [Ruminococcus] torques group, Ruminiclostridium 9, Catenibacterium and [Eubacterium] fissicatena group. Spearman's correlation analysis revealed significant correlations between changes in the gut microbiota and atherosclerosis-related indices. The results demonstrated that the alleviating effects of MLM structured lipids supplementation on AS in high-fat diet-fed ApoE −/− mice were closely related to reshaping the composition of the gut microbiota.